Application of response surface methodology for parameter optimization of aluminum 7075 thixoforming feedstock billet production - Megalingam, A; Asnul Hadi, Ahmad; Nasrul Azuan, Alang; Juliawati, Alias; Nur Azhani, Abd Razak (Springer US, 2023)
This paper aims to present the experimental work to formulate optimum processing parameters of the direct thermal method (DTM) using response surface methodology (RSM) for high-quality feedstock billet production. The DTM is one of the techniques which is used to produce aluminum 7075 alloy feedstock billets with globular microstructures for thixoforming operations. Based on the central composite design (CCD) techniques, 13 experiments were performed using two factors and levels. Pouring temperature parameters in CCD varied from 645 to 685 °C, with holding times ranging from 20 to 60 s. The size of the microstructures of the produced feedstock billets was measured, and the different parameter combinations were analyzed in detail by RSM. Moreover, the distribution of elements and the impact of primary and secondary phases on microstructures were examined by scanning electron microscopy (SEM)). Statistical analysis showed that R2 values of circularity and aspect ratio were 0.96 and 0.97 and meanwhile probability values (p < 0.05), (F-value > p-value) at 95% confidence level, with an acceptable error percentage. RSM results showed that a pouring temperature of 665 °C and a holding time of 60 s produced the optimum globular microstructure. The grain diameter, circularity, and aspect ratio values were 61.12 µm, 0.707, and 1.44, respectively. Moreover, the predicted and experimental values are in good agreement. These experimental results that used the RSM explained the effects of the various combination parameters in detail using a limited number of experiments and have successfully identified the optimum parameters.